Pengintegrasian Soft Skills pada Setiap Pembelajaran: (Sebagai Upaya Menghadapi Tantangan Revolusi Industri 4.0 / Era Disrupsi) - Darwanto D; Nova Sari (Eksponen, 2020)
Face the challenges of the disruption era, efforts must be made early to planting soft skills in each student. One such effort is integrate soft skills in every learning at every level of formal education. A person’s greatest success is only influenced by 20% of hard skills and 80% of soft skills. The biggest problems in education showed that there is a soft skills crisis in students. Learning, Industrial Revolution 4.0, Soft Skills.